VILLAGE FUND ALLOCATION MANAGEMENT SYSTEM IN TINGGIMAE VILLAGE, BAROMBONG DISTRICT, GOWA REGENCY, SELATAN SULAWESI - Noor, Muh Yasin (Jurnal Ekonomi Balance, 2018)
Village Fund Allocation Management System in Tinggimae Village, Baromobong District, Gowa Regency, South Sulawesi. This study aims to determine how the village fund allocation management system is in Tinggimae village, Barombong Subdistrict, Gowa Regency, South Sulawesi. The type of research data used is qualitative data using a qualitative descriptive research design. Data collection methods are used with questionnaire, interview and documentation techniques. This study was conducted for three months from December 2017 to February 2018. The results of the study showed no significant effect of education on the performance of teachers at Majene 2 High School and there was a significant influence on work discipline on the performance of Majene 2 High School teachers.